La paz del mundo y la perspectiva Islámica - Bahram Navazeni; Alireza Nabawi (Universidad Hemisferios, 2017)
World peace as an ideal situation associated with freedom and prosperity refers to a situation in which all the people of the world work together to avoid war and violence. This article is aimed at analyzing the formation and activation of the United Nations as a momentum of the international community. In Iran, after the Islamic Revolution of 1979 there has been an emphasis on dignity, human values and freedom, with responsibility before God. The Iranian constitution is opposed to all cruelty, oppression, domination and submission, and heralds the provision of social and political freedoms, within the limits of law. The present article is intended to use the descriptive-analytical method in order to study the positive concept of world peace. With the help of library resources and legal documents the present paper aims to explain the sustainable initiatives to creating of world peace contained in the Iranian Constitution, based on the Quranic verses and its interpretations of Ghotb in Egypt and Imam Khomeini in Iran. Among such principles of the constitution, is human happiness in Iran, in the entire Islamic Ummah, and in the whole human community. The Constitution also proclaims independence, freedom, the rule of justice and truth for all peoples.